2018
DOI: 10.1063/1.5027253
|View full text |Cite
|
Sign up to set email alerts
|

Transition path theory from biased simulations

Abstract: Transition Path Theory (TPT) provides a rigorous framework to investigate the dynamics of rare thermally activated transitions. In this theory, a central role is played by the forward committor function (), which provides the ideal reaction coordinate. Furthermore, the reactive dynamics and kinetics are fully characterized in terms of two time-independent scalar and vector distributions. In this work, we develop a scheme which enables all these ingredients of TPT to be efficiently computed using the short non-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 54 publications
0
19
0
Order By: Relevance
“…rMD-based methods have been successfully applied to simulate protein folding and other conformational transitions (17,18). However, this scheme provides a sampling of the transition path ensemble only if the biasing force is applied along a reliable reaction coordinate (19). Therefore, the first step towards developing our rMD simulation was to build a statistical model to identify the reaction coordinate of the process.…”
Section: Resultsmentioning
confidence: 99%
“…rMD-based methods have been successfully applied to simulate protein folding and other conformational transitions (17,18). However, this scheme provides a sampling of the transition path ensemble only if the biasing force is applied along a reliable reaction coordinate (19). Therefore, the first step towards developing our rMD simulation was to build a statistical model to identify the reaction coordinate of the process.…”
Section: Resultsmentioning
confidence: 99%
“…The BF variational principle allows the subsequent identification of the rMD transition pathways with the highest probability to occur in the absence of biasing force. It has been rigorously shown that rMD yields realistic transition path ensembles when the CV used in the biasing force is an ideal reaction coordinate (RC), namely the committor function [16]. However, whenever a reasonable proxy of the RC is available, then the BF variational scheme enables to keep the systematic errors of rMD to a minimum.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that SCPS provides a rigorous mean-field approximation of the unbiased Langevin dynamics, even when the initial guess of reaction coordinate is suboptimal [16,22]. Thus, SCPS provides a much better tool than BF to investigate structural reactions in which the reaction coordinate is poorly known, thus including prion propagation.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, more elaborate statistical methods have been proposed for recovering equilibrium distributions from SCPS and BF nonequilibrium simulations. For example, a recently proposed scheme makes it possible to sample the Boltzmann distribution in the transition region by means of specific ratchetand-pawl simulations (77). To date, however, these techniques have only been validated against MD simulations for simple systems, and further validation is required to assess their accuracy for realistic and biologically relevant systems.…”
Section: All-atom-enhanced Sampling Based On a Native-centric Biasingmentioning
confidence: 99%